A Methodological Note on the Construction of High Frequency Macroeconomic Series: Evidence from Tunisia - Salem, Hathroubi (Asian Journal of Economics and Empirical Research, 2015)
This note aims to formulate and to apply a combined method of the Loss Quadratic Function of Denton and the Best Linear Unbiased Estimator of Chow-Lin to construct quarterly data for Tunisia. High frequency series for GDP and total investment are obtained from related series which exist in high (quarterly) and low (annual) frequencies for the period 1970-2013. Tunisia began publishing quarterly GDP only since 2001Q1. We use these series to compare our estimates to those published by the Tunisian National Institute of Statistic (INS). Results show that the combined method generates high quality quarterly series.